DIGITAL TRANSFORMATION AND ITS IMPACT ON PUBLIC SECTOR ACCOUNTING QUALITY IN DEVELOPING ECONOMIES - Shella Gilby Sapulette; Franco Benony Limba (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze the impact of digital transformation on the quality of public sector accounting in developing economies using a literature review approach. The research systematically examines and synthesizes relevant academic articles, policy reports, and prior studies published in recent years to understand the relationship between digital technology adoption and improvements in accounting practices. Digital transformation, characterized by the integration of technologies such as cloud computing, big data analytics, and e-government systems, has played a significant role in enhancing the efficiency, transparency, and accountability of public financial management. The findings of this study indicate that the implementation of digital systems contributes to higher accounting quality through improved data accuracy, real-time reporting, and better internal control mechanisms. However, the study also identifies several challenges, including technological disparities, limited human resource competencies, and institutional constraints that may limit the effectiveness of digital transformation initiatives. Therefore, strengthening digital infrastructure, improving technical skills, and establishing supportive regulatory frameworks are essential to optimize the benefits of digital transformation in the public sector. This study provides valuable insights for policymakers and researchers in advancing the quality of public sector accounting in developing countries.